Developing a resilient supply chain strategy during 'boom' and 'bust'. Issue 7 (10th June 2016) - Purvis, L.; Spall, S.; Naim, M.; Spiegler, V.
Abstract: Supply chain resilience is often perceived as highly desirable, as it increases a firm's readiness in dealing with risks that can emerge from the customers' side, the suppliers' side, the internal processes adopted and the supply chain integration mechanisms employed. However, though practitioners responsible for the design and management of supply networks often see resilience as highly desirable, they also see the direct trade-off being cost. An in-depth qualitative single case is presented in this study, using an iterative cycle between theory and practice to delve into the experiences of the case company and various concepts from the literature. A framework for the development and implementation of a resilient supply chain strategy is proposed, which illustrates the relevance of various management paradigms (robustness, agility, leanness and flexibility) in increasing a company's ability to deal with disturbances emerging from its supply chain. The paper advances theory and closes some of the gaps in the literature with regard to the ways certain management paradigms could be combined in practice in order to develop a supply chain resilience strategy.